2016
DOI: 10.1590/18069657rbcs20160007
|View full text |Cite
|
Sign up to set email alerts
|

A Classification for a Geostatistical Index of Spatial Dependence

Abstract: ABSTRACT:In geostatistical studies, spatial dependence can generally be described by means of the semivariogram or, in complementary form, with a single index followed by its categorization to classify the degree of such dependence. The objective of this study was to construct a categorization for the spatial dependence index (SDI) proposed by Seidel and Oliveira (2014) in order to classify spatial variability in terms of weak, moderate, and strong dependence. Theoretical values were constructed from different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 31 publications
0
46
0
3
Order By: Relevance
“…The ratio between the nugget effect and the sill defines the level of spatial dependence of the data. The dependence can be characterized as strong, moderate or weak (CRESSIE and HARTFIELD, 1966;SEIDEL et al, 2016;SEIDEL and OLIVEIRA, 2014). More information of these geostatistical parameters can be found in Cressie (1993), Isaaks and Srivastava (1989), Govaerts (1997), Chilès and Delfiner (1999) and Journel (1978).…”
Section:  mentioning
confidence: 99%
“…The ratio between the nugget effect and the sill defines the level of spatial dependence of the data. The dependence can be characterized as strong, moderate or weak (CRESSIE and HARTFIELD, 1966;SEIDEL et al, 2016;SEIDEL and OLIVEIRA, 2014). More information of these geostatistical parameters can be found in Cressie (1993), Isaaks and Srivastava (1989), Govaerts (1997), Chilès and Delfiner (1999) and Journel (1978).…”
Section:  mentioning
confidence: 99%
“…In the spatial dependence analysis, the spatial dependence index was calculated and classified (Seidel & Oliveira, 2016), in which the spatial dependence for the spherical model is: considered weak for values up to 7%, moderate when between 7% and 15%, and strong when above 15%; for the exponential model it is: considered weak for values up to 6%, moderate between 6% and 13% and strong if above 13%; and for the Gaussian model it is: considered weak for values up to 9%, moderate between 9% and 20% and strong if above 20% (Table 1), by Equation (2):…”
Section: /10mentioning
confidence: 99%
“…The SDI index has a positive asymmetric sampling distribution (SEIDEL & OLIVEIRA, 2016) Results obtained from the correlations indicated that the SDI is able to capture, in an intense way, the behavior of the range and the when evaluating the spatial dependence, evidencing also the behavior in the horizontal sense of the semivariogram. This is an important feature of the SDI index, which differentiates it from other indexes in the literature, since according to FERRAZ et al (2012) the range has a considerable role in determining the limit of spatial dependence.…”
mentioning
confidence: 93%
“…The data were obtained from 25 articles, published from 2006 to 2015 and made available on the Scielo Brazil portal, with application of Geostatistics in Soil attributes, used and cited in SEIDEL & OLIVEIRA (2016). From the papers, the following information was collected for each attribute: model of semivariogram adjusted, estimated range (a), estimated nugget effect (C 0 ), estimated contribution (C 1 ), estimated sill (C=C 0 +C 1 ), maximum sample distance (MD), soil type, type of attribute (chemical, physical or mineralogical) and soil layer (depth).…”
mentioning
confidence: 99%
See 1 more Smart Citation